2014
DOI: 10.1002/ijc.29323
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasound for predicting pathologic response during neoadjuvant therapy for breast cancer

Abstract: Early assessment of response to neoadjuvant chemotherapy (NAC) for breast cancer allows therapy to be tailored; however, optimal response assessment methods have not been established. We estimated the accuracy of ultrasound (US) to predict pathologic complete response (pCR) using common response criteria and pCR definitions, and estimated incremental accuracy over known prognostic variables. Participants undergoing US after two cycles in the GeparTrio trial randomised to no change in NAC were eligible. US resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
(82 reference statements)
1
29
0
1
Order By: Relevance
“…Many studies have investigated monitoring of neoadjuvant therapeutic response, and pathologic response assessment has been widely used as an end point reference (3,4,(6)(7)(8)(9)(10). However, the definition of pathologic complete response varies among studies, and the prognostic value of pathologic complete response depends on breast cancer type (6,8,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated monitoring of neoadjuvant therapeutic response, and pathologic response assessment has been widely used as an end point reference (3,4,(6)(7)(8)(9)(10). However, the definition of pathologic complete response varies among studies, and the prognostic value of pathologic complete response depends on breast cancer type (6,8,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal method for monitoring the response to neoadjuvant therapy has not been established (6). Ultrasonography (US), magnetic resonance (MR) imaging, and positron emission tomography (PET)/ computed tomography (CT) have been investigated as monitoring tools but are not standardized (7)(8)(9). Currently, clinical breast examination, mammography, US, and, in selected patients, MR imaging are used at diagnosis, during chemotherapy, and after completion of (24).…”
mentioning
confidence: 99%
“…Recently, Lee et al [ 22 ] summarized inaccuracies among current practical tools used to evaluate residual tumor volumes in response to NCT and demonstrated that two-dimensional and three-dimensional ultrasound and breast MRI show similar performances for the estimation of residual breast cancer volume and prediction of pCR. In a retrospective analysis of patients enrolled in the GeparTrio trial, ultrasound showed a high sensitivity for predicting ypT0 and ypN0 and modestly improved the prediction of pCR by patient characteristics, which was concluded to be a potentially useful modality for early prediction of pCR, despite breast MRI not being included in the study [ 23 ]. In addition, ultrasound provides clinical advantages over MRI including lower complexity, easier accessibility, shorter procedure time, easier interpretation, cheaper costs, and lack of the hazards associated with contrast agents [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained (details in Appendix A). However, because of its low cost and accessibility, US has been utilized and evaluated in several studies (9)(10)(11)(12). In the GepharTrio trial of 2090 patients bidimensional US measurements at EOC2 were used to classify response and randomize patients to treatment with 6 vs 8 cycles of NAC (11).…”
Section: Resultsmentioning
confidence: 99%